Indigenous Health Rights in Indonesia: Legal and Policy Challenges to Healthcare Access (Indonesian Health Justice Review, 2024)
Indigenous communities in Indonesia face significant challenges in accessing healthcare services, rooted in legal and policy gaps that hinder the recognition and protection of their health rights. This study explores the intersection of indigenous health rights with Indonesia's healthcare system, focusing on the legal and policy frameworks that govern healthcare access for indigenous populations. Using a qualitative approach, the research analyzes national health policies, local government regulations, and interviews with indigenous leaders, healthcare providers, and policymakers. Findings suggest that while Indonesia’s legal framework includes provisions for indigenous rights, implementation remains inconsistent, and indigenous groups continue to experience barriers such as cultural insensitivity in healthcare delivery, language barriers, and lack of accessible facilities. Moreover, traditional health practices are often marginalized by the formal healthcare system, further exacerbating health disparities. The paper advocates for reforms in both policy and practice, emphasizing the need for culturally appropriate healthcare, improved healthcare accessibility, and stronger legal protections to ensure that indigenous communities have equal access to health services. Recommendations include enhancing the participation of indigenous leaders in health policy development and integrating indigenous health knowledge into the national healthcare system.